Abolitionist geographies - Schoolman, Martha (2014)
"Traditional narratives of the period leading up to the Civil War are invariably framed in geographical terms. The sectional descriptors of the North, South, and West, like the wartime categories of Union, Confederacy, and border states, mean little without reference to a map of the United States. In Abolitionist Geographies, Martha Schoolman contends that antislavery writers consistently refused those standard terms. Through the idiom Schoolman names 'abolitionist geography,' these writers instead expressed their dissenting views about the westward extension of slavery, the intensification of the internal slave trade, and the passage of the Fugitive Slave Law by appealing to other anachronistic, partial, or entirely fictional north-south and east-west axes. Abolitionism's West, for instance, rarely reached beyond the Mississippi River, but its East looked to Britain for ideological inspiration, its North habitually traversed the Canadian border, and its South often spanned the geopolitical divide between the United States and the British Caribbean. Schoolman traces this geography of dissent through the work of Martin Delany, Ralph Waldo Emerson, William Wells Brown, and Harriet Beecher Stowe, among others. Her book explores new relationships between New England transcendentalism and the British West Indies; African-American cosmopolitanism, Britain, and Haiti; sentimental fiction, Ohio, and Liberia; John Brown's Appalachia and circum-Caribbean marronage. These connections allow us to see clearly for the first time abolitionist literature's explicit and intentional investment in geography as an idiom of political critique, by turns liberal and radical, practical and utopian"--
Introduction: What Is Abolitionist Geography? -- Emerson's Hemisphere -- August First and the Practice of Disunion -- William Wells Brown's Critical Cosmopolitanism -- Uncle Tom's Cabin's Anti-Expansionism -- The Maroon's Moment, 1856/1861.
Keywords: Delany, Martin Robison, -- 1812-1885 -- Criticism and interpretation; Emerson, Ralph Waldo, -- 1803-1882 -- Criticism and interpretation; Brown, William Wells, -- 1814?-1884 -- Criticism and interpretation; Stowe, Harriet Beecher, -- 1811-1896 -- Criticism and interpretation; Antislavery movements -- United States -- History -- 19th century; Abolitionists -- United States -- History -- 19th century; Geography in literature; Antislavery movements in literature; African Americans in literature; American literature -- 19th century -- History and criticism; LITERARY CRITICISM / American / General; SOCIAL SCIENCE / Ethnic Studies / African American Studies; SOCIAL SCIENCE / Human Geography